A new scoring system facilitating diagnosis of oral squamous malignancy on biopsy specimens - Cheng-Lin Wu; Cheng-Chih Huang; Shang-Yin Wu; Shih-Sheng Jiang; Fang-Yu Tsai; Jenn-Ren Hsiao (BMC, 2022)
Abstract Background Morphological evaluation of oral mucosal biopsy is sometimes inconclusive, which may delay the diagnosis and treatment of oral squamous malignancy. Immunohistochemical biomarkers denoting oral squamous malignancy would be clinically helpful in such scenario. Methods We first studied the expression patterns of four potential biomarkers (cytokeratin 13, cytokeratin 17, Ki-67 and laminin 5 gamma 2 chain) in an exploratory cohort containing 54 surgical specimens from confirmed oral squamous malignancies. A pattern score was assigned to each specific expression pattern of these four biomarkers. A total score from each specimen was then calculated by summing up the four pattern scores. A cut-off value of total score denoting oral squamous malignancy was then determined. Another 34 oral squamous malignancies that were misdiagnosed as non-malignant lesions on their pre-treatment biopsies were used as a validation cohort to test the clinical utility of this scoring system. Results In the exploratory cohort, fifty-two (96%) of the 54 confirmed oral squamous malignancies had a total score of 9 and above. In the validation cohort, thirty-one (91%) of the 34 pre-treatment oral biopsy specimens also had a total score of 9 or above, supporting the feasibility of using this scoring system to predict immediate risk of oral squamous malignancy. Conclusions Our four-biomarker "oral squamous malignancy scoring system" provides reliable prediction for immediate risk of oral squamous malignancy on pre-treatment oral biopsies.